BETWEEN THE GOOD NEIGHBOR POLICY AND THE LATIN AMERICAN “BOOM”:: BRAZILIAN LITERATURE IN THE UNITED STATES - Livingstone, Victoria (Belas Infiéis, 2015)
This article studies the translation of Brazilian literature in the United States between 1930 and the end of the 1960s. It analyzes political, historical and economic factors that influenced the publishing market for translations in the U.S., focusing on the editorial project of Alfred A. Knopf, the most influential publisher for Latin American literature in the U.S. during this period, and Harriet de Onís, who translated approximately 40 works from Spanish and Portuguese into English. In addition to translating authors such as João Guimarães Rosa and Jorge Amado, de Onís worked as a reader for Knopf, recommending texts for translation. The translator’s choices reflected the demands of the market and contributed to forming the canon of Brazilian literature translated in the United States.